PEMANFAATAN TEKNOLOGI AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN PENGENALAN SATWA DI SEKOLAH DASAR - Kinanti Ika Maharani; Adam Sekti Aji (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
The unsatisfactory quality of the teaching and learning process in the classroom can be ascribed to the students' limited attention during the animal introduction classes, which is further intensified by the lack of instructional media or resources. The predominant dependence on educators and printed educational materials as the principal means of accessing learning resources exerts a substantial impact on students' levels of motivation and their academic performance. One possible strategy for increasing student engagement entails the integration of educational applications that employ Augmented Reality (AR) technology. Augmented Reality (AR) is a technical advancement that replicates a virtual environment that closely resembles the physical world. This is achieved by employing the marker approach to generate three-dimensional (3D) objects. The current investigation employed a methodology based on marker tracking. This study produces an educational application that includes an introductory section on animals and concise information on several animal species. The primary objective of this application is to engage and captivate students by presenting the material in an engaging manner. The software application is designed to be compatible with the Android operating system. The application we created has proven to have the potential to display three-dimensional representations of animal objects graphically, complemented by voice explanations. The Animal Tracker application has the capacity to demonstrate the capabilities of Augmented Reality proficiently.